Analisis Hubungan Kinerja Lingkungan dan Profitabilitas Terhadap Nilai Perusahaan - Rizqy Aiddha Yuniawati (Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2022)
This study aims to examine the relationship between environmental performance and profitability on firm value. The method used in this research is a descriptive research method with a quantitative approach. The population in this study is textile companies listed on the Indonesia Stock Exchange. The sampling technique in this study used purposive sampling, companies listed on the Indonesia Stock Exchange and published financial statements for 2018-2019, and participated in the Company Rating Program. The type of data used is secondary data. The analytical model used is multiple linear regression with partial hypothesis test (t) and simultaneous test (F). Environmental Performance is measured by the company's performance in PROPER. Profitability is measured by return on assets (ROA). Firm value can be calculated by Tobin's Q analysis. The results of this study indicate that environmental performance and profitability have no partial effect on firm value. Furthermore, the test results simultaneously environment and profitability affect firm value. This research contributes to the environmental accounting literature, especially for sustainable development. This research is expected to provide consideration to further increase awareness of environmental performance by making accurate principles.